Noise annoyance predicts symptoms of depression, anxiety and sleep disturbance 5 years later. Findings from the Gutenberg Health Study. (8th February 2020) - Beutel, Manfred E; Brähler, Elmar; Ernst, Mareike; Klein, Eva; Reiner, Iris; Wiltink, Jörg; Michal, Matthias; Wild, Philipp S; Schulz, Andreas; Münzel, Thomas; Hahad, Omar; König, Jochem; et al.
Abstract: Background: Cross-sectional studies have shown that noise annoyance is strongly associated with mental distress, however, its long-term effects on mental health is unknown. We therefore investigated whether noise annoyance predicts depression, anxiety and sleep disturbance in a large, representative sample 5 years later. Methods: We investigated longitudinal data of N = 11 905 participants of the Gutenberg Health Study, a population-based, prospective, single-centre cohort study in mid-Germany (age at baseline 35–74 years). Noise annoyance was assessed at baseline and 5-year follow-up (sources: road traffic, aircraft, railways, industrial, neighbourhood indoor and outdoor noise; and day vs. nighttime). Depression, anxiety and sleep disturbance were assessed using the Patient Health Questionnaire-9 and Generalized Anxiety Disorder-2. Participants suffering from depression, anxiety or sleep disturbance at baseline were excluded from the respective multivariate analyses of new onset at follow-up. Results: General noise annoyance remained stable. Daytime noise annoyance predicted new onset of depressive, anxiety symptoms (also nighttime annoyance) and sleep disturbance (beyond respective baseline scores). Additional predictors were female sex, lower age and low socioeconomic status (SES). Regarding specific sources, daytime baseline aircraft annoyance predicted depression and anxiety. Sleep disturbance was most consistently predicted by neighbourhood annoyance (baseline and follow-up) and follow-up annoyance by aircraft (night) and road traffic (day and night). Conclusions: We identified current and past noise annoyances as risk factors for mental distress and sleep disturbance. Furthermore, women, younger adults and those with lower SES are particularly susceptible to noise annoyance. Our results indicate the need to provide regulatory measures in affected areas to prevent mental health problems.